Estimulación visual temprana en neonatos con baja visión, revisión bibliográfica - Ariza González, Sileny Dayana (Universidad Antonio Nariño, 2022)
Eye and systemic diseases, such as albinism, congenital malformations, brain pathway deficiencies, nystagmus and others, cause great damage in newborns, this triggers visual disturbances that lead to low vision in the newborn.